The effect of internal forced displacement on small and medium enterprises in the host community, in case of Amhara region, Ethiopia - Tefera Getachew Dagnachew (Journal of Innovation and Entrepreneurship, 2023)
Ethiopia is highly challenged by the growing ethnicity-based conflict and large numbers of people are forcibly displaced from their origin. This study examines the effect of growing internal forced displacements on small and medium enterprises in the Amhara region, Ethiopia. The study used firm-level data for the years between 2015 and 2021. To analyze the effect of IDPs, the study used a panel-instrumental approach. The estimated result finds that large forced IDPs affect enterprises' production. Small enterprises are highly affected by IDPs compared to medium enterprises, and this is due to the greater influence of the informal sector on small enterprises.
Keywords: 650; Enterprises exit; Forced displacement; Informality; Small enterprises